Estimates of approximative characteristics of the classes $B^{Ω}_{p,θ}$ of periodic functions of several variables with given majorant of mixed moduli of continuity in the space $L_{q}$ - Fedunyk-Yaremchuk, O.V.; Hembars'ka, S.B. (Carpathian Mathematical Publications, 2019)
In this paper, we continue the study of approximative characteristics of the classes $B^{Ω}_{p,θ}$ of periodic functions of several variables whose majorant of the mixed moduli of continuity contains both exponential and logarithmic multipliers. We obtain the exact-order estimates of the orthoprojective widths of the classes $B^{Ω}_{p,θ}$ in the space $L_{q},$ $1≤ p<q<∞,$ and also establish the exact-order estimates of approximation for these classes of functions in the space $L_{q}$ by using linear operators satisfying certain conditions.